Dhaka megacity : geospatial perspectives on urbanisation, environment and health - Dewan, Ashraf (Dordrecht ; New York : Springer, 2014)
"The book Dhaka Megacity: Geospatial Perspectives on Urbanisation, Environment and Health presents the use of geospatial techniques to address a number of environmental issues, including land use change, climatic variability, urban sprawl, population density modelling, flooding, environmental health, water quality, energy resources, urban growth modelling, infectious diseases and the quality of life. Although the work is focused on the Megacity of Dhaka in Bangladesh, the techniques and methods that are used to research these issues can be utilized in any other areas where rapid population growth coupled with unplanned urbanization is leading to environmental degradation. The book is useful for people working in the area of Geospatial Science, Urban Geography, Environmental Management and International Development. Since the chapters in the book cover a range of environmental issues, this book describes useful tools for assisting informed decision making, particularly in developing countries"--Provided by publisher
-- 1. Introduction / Robert J. Corner and Ashraf M. Dewan -- 2. From a town to a megacity: 400 years of growth / Sohel J. Ahmed, Kh. Md. Nahiduzzaman and Glen Bramley -- 3. Spatiotemporal patterns of population distribution / Robert J. Corner, Emmanuel T. Ongee and Ashraf M. Dewan -- 4. Climatic variability / Yusuke Yamane, Masashi Kiguchi, Toru Terao, Fumie Murata and Taiichi Hayashi -- 5. Monitoring and prediction of land-use and land-cover (LULC) change / Robert J. Corner, Ashraf M. Dewan -- 6. Spatiotemporal analysis of urban growth, sprawl and structure / Ashraf M. Dewan and Robert J. Corner -- 7. Key driving factors influencing urban growth: spatial-statistical modelling with CLUE-s / Sohel J. Ahmed, Glen Bramley and Peter H. Verburg -- 8. Analysis of urban development suitability / Calit Chakma -- 9. Impact of land use change on flooding patterns / Takeo Onishi, Tahmina Khan and Ken Hiramatsu -- 10. Flood vulnerability and risk assessment with spatial multi-criteria evaluation / Akiko Masuya -- 11. Supplementing electrical power through solar PV systems / Md. Humayun Kabir and Wilfried Endlichter -- 12. Impact of land use and land cover changes on urban land surface temperature Ashraf M. Dewan and Robert J. Corner -- 13. Illustrating quality of life (QOL) / Ashraf M. Dewan, Kamrun Nahar, and Yohei Kawamura -- 14. Exploring crime statistics / Ashraf M. Dewan, Md. Rafiqul Haider, and Md. Ruhul Amin -- 15. Environmental problems and governance / Salim Momtaz and S.M. Zobaidul Kabir -- 16. Assessing surface water quality using Landsat TM and In-Situ data: an exploratory analysis / Razia A. Chowdhury, Towhida Rashid and Sirajul Hoque -- 17. Emissions from the brick manufacturing industry / Sarath K. Cuttikunda -- 18. Rainfall dependence of hospital visits of aeromonas-positive diarrhoea / Masahiro Hashizume, Abu S.G. Faruque and Ashraf M. Dewan -- 19. Modelling spatiotemporal patterns of typhoid cases between 2005 and 2009 using spatial statistics / Ashraf M. Dewan, Robert J. Corner and Masahiro Hashizume -- 20. Spatiotemporal analysis of dengue infection between 2005 and 2010 / Sarwa Ali, Robert J. Corner and Masahiro Hashizume
Includes bibliographical references and index
Keywords: Environmental management -- Bangladesh -- Dhaka; Urbanization -- Bangladesh -- Dhaka; Dhaka (Bangladesh) -- Geographic information systems